Formation of 4(5)-methylimidazole in processed meat and in glucose amino acid model system - Hussain, Faris A. (Kansas State University, 2015)
The International Agency for Research on Cancer (IARC) has classified 4(5)-methylimidazole (4-MeI) as a possible human carcinogen. Also, the National Toxicology Program (NTP) has concluded that 4-MeI is a probable cancer causing agent. Even though 4-MeI has been detected in several processed foods no research has been conducted to measure levels of 4-MeI in processed meat. A method using isobutylchloroformate (IBCF) and gas chromatography mass-spectrometry (GC-MS) was developed to detect and quantify 4-MeI in processed meat products. Levels of 4-MeI ranged from 0.04 to 1.01 μg/g with recovery of 94.76 to 103.94%. Formation of 4-MeI in glucose-amino acid model system was studied. [subscript]D-Glucose (Glu) was mixed individually in equimolar concentrations of 0.05, 0.1, or 0.15 M and equal volume with [subscript]L-Alanine (Ala), [subscript]L-Arginine (Arg), Glycine (Gly), [subscript]L-Lysine (Lys), and [subscript]L-Serine (Ser); and the mixtures were heat treated at 60, 120, and 160°C for 1 h. Among all tested amino acids, Glu-Arg produced the highest level of 4-MeI. The Glu-Lys model system showed higher browning and lower concentrations of 4-MeI. The effect of ascorbic acid (ASA), a strong antioxidant, was studied in the Glu-Arg model system. Four concentrations of ASA (0.0375, 0.075, 0.15, and 0.3 M) were mixed with 0.15 M equimolar of Glu-Arg and heat treated at 160°C for 1h. ASA inhibited formation of 4-MeI by 40.29, 69.94, 75.13, and 96.25% for the 0.0375, 0.075, 0.15, and 0.3 M concentrations. Contrarily, ascorbic acids increased the browning in all treatments compared to control treatment by 10.67, 15.47, 18.4, and 28.8% for the 0.0375, 0.075, 0.15, and 0.3 M concentrations. Adding ASA to processed food may reduce formation of 4-MeI and increase the browning that is a desired attribute to processed meat products.
Keywords: Caramel color; 4-Methylimidazole; meat products; Food Science (0359)